Did large Algerian enterprises pay an equitable tax contribution? Evidence from Longitudinal Data - Otmane Rachedi, Fatma Zohra (Technium Social Sciences Journal, 2022)
This research paper used financial statements information to measure Effective Tax Rates (ETRs) , which represent the proportion of profits incurred by large Algerian enterprises as a tax burden during a given financial year, and compared them with the Statutory Tax Rates (STRs) imposed by Algerian law. The purpose of the study was to determine whether, in the context of a political economy, that tax contribution respects the principle of Tax Equity. It employed a sample of 114 enterprises for the 2012 to 2018 financial year. The variability between ETRs and STR indicates the intervention of elements that cause differences between the accounting result and the taxable base. Higher ETRs mean that these enterprises are under fiscal pressure and lower ETRs mean that the tax burden effectively supported is inconsistent with these enterprises’ profits level. The findings indicate that there are considerable differences in the tax burden borne by these enterprises and that most ETRs were lower than STRs. According to the results of this study, we conclude that large Algerian enterprises have not paid an equitable tax contribution.